A new species of the genus Tarehylava Stroiński, 2021 (Hemiptera: Fulgoromorpha: Ricaniidae) from southern Madagascar - Gnezdilov, Vladimir M. (Zootaxa, 2024)
A new species of the ricaniid genus Tarehylava Stroiński, 2021, T. gorgona sp. nov., is described from the Androy Region of Madagascar. Male genitalia structure of the genus Tarehylava is described for the first time. The relationships of Tarehylava within Ricaniidae are discussed.